Multi-purpose cooperatives towards people empowerment and development - Jadloc, Zosimo A. 1932- (Quezon City Giraffe Books, 2001)
A handbook designed to help community organizers, officers of cooperatives, group leaders and prospective cooperative members in their involvement in the activities in the cooperative movement. It contains guidelines on how members of a democratic society can be liberated and empowered to avoid financial and political exploitation.
Purpose: "This book is about modern cooperatives based on the need to liberate certain members of any human society from financial and political exploitation by empowering said members."
Contents: History of cooperatives. Organization and cooperation. Rules. Case studies on selected cooperatives. Conclusions and recommendations.
Keywords: Cooperative societies -- Handbooks, manuals, etc